GIS-based Forecast of Landscape Changes with the Ito Land Readjustment Project - Hiroshi Tatsumi; Satoshi Toi; Kazunari Tanaka; Sanpei Yamashita; Yoshitaka Kajita (European Regional Science Association (ERSA), 2005)
The purpose of the present research is to attempt consolidation of geographic information into the GIS regarding the Ito Land Readjustment Project presently being implemented in northern Kyushu in Japan, and forecast the landscape changes before/after comparison of the project. First, the topographic map, 50-meter mesh digital map (elevation), aerial photograph, land use map, project plan, land use zone plan, district plan, substitute lot plan and other geographic information of the project district were collected from various sources and systematized. Thereafter the data were aggregated using ArcGIS. Next, building and structure data before and after the project were prepared and height data of these buildings and structures were combined with the land elevation data. Then, the major view point fields in the district were selected, to examine the extent of the change of the visibility areas from these view point fields before and after the project. Moreover, focusing on the mountains in the visibility areas, we forecasted how much the visibility area of the mountains would decrease at each view point field after construction of the buildings and structures in the project implementation. Finally, we showed 3-D images of the project district using ArcScene, and investigated the extent of visibility of the mountain range sky line from each view point field as before/after comparison of the project.
Keywords: 330